DETECÇÃO DA ÁREA DE COBERTURA EM REDES WIRELESS USANDO À METAHEURÍSTICA SIMULATED ANNEALING - Vlieger, Maira T. d.; Sausen, Paulo S.; Sausen, Airam; Reckziegel, Ciro; Sawicki, Sandro (Salão do Conhecimento, 2013)
Resumo